Parkinson's Disease Research on the African Continent: Obstacles and Opportunities - Dekker, Marieke C. J.; Coulibaly, Toumany; Bardien, Soraya; Ross, Owen A.; Carr, Jonathan; Komolafe, Morenikeji (Frontiers in Neurology, 2020)
The burden of Parkinson’s disease (PD) is becoming increasingly important in the context of an ageing African population. Although PD has been extensively investigated with respect to its environmental and genetic aetiology in various populations across the globe, studies on the African continent remain limited. In this Perspective article, we review some of the obstacles that are limiting research and creating barriers for future studies. We summarise what research is being done in four sub-Saharan countries and what the key elements are that are needed to take research to the next level. We note that there is large variation in neurological and genetic research capacity across the continent, and many opportunities for unexplored areas in African PD research. Only a handful of countries possess appropriate infrastructure and personnel, whereas the majority have yet to develop such capacity. Resource-constrained environments strongly determines the possibilities of performing research locally, and unidirectional export of biological samples and genetic data remains a concern. Local-regional partnerships, in collaboration with global PD consortia, should form an ethically appropriate solution, which will lead to a reduction in inequality and promote capacity building on the African continent.